If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-9(v+7)
We move all terms to the left:
9-(-9(v+7))=0
We calculate terms in parentheses: -(-9(v+7)), so:We get rid of parentheses
-9(v+7)
We multiply parentheses
-9v-63
Back to the equation:
-(-9v-63)
9v+63+9=0
We add all the numbers together, and all the variables
9v+72=0
We move all terms containing v to the left, all other terms to the right
9v=-72
v=-72/9
v=-8
| -5(v+3)+16=-4 | | 0.3=-x/0.556+2x | | m+27=-25 | | 4.20=0.6x | | 4x+60+6x+40=360 | | 4d+(15=3d) | | 2y+(22/8y)=190 | | y+14-3y=86 | | -29=-5(r-8)-9 | | 3-m/6=12 | | x+5=20–2x | | 4w-3+3(2w+1)=-2(w=7) | | 4n-2(3-n)=18 | | 2d-46=3d | | -2/5=u+6 | | 1.5(2t−6)=3t−6 | | x^2+6x-50=8x+30 | | 5x+-6=3x+4 | | -6x=-8x+18 | | 3x−(x+2)=18 | | 8=a/3-9 | | 24x+247=235 | | 3x-12=3(x- | | 10x+16^=6x+20 | | 1000(9x−10)=50(768+100x) | | 24x+247=35 | | 10x−3(2x+2)=30 | | -4a+24=-3 | | 12d-46=3d | | 10-2(x+6)=0 | | 8(s-5)=24 | | (16x+53)-(9-2x)+(4x+3)-(1x-45)=(45x+13) |